The Facilitation of Design Students’ Spatial Perception in Study Process - Karlsone, Inguna (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2015)
Spatial thinking is a considerable structural component of design students’ professional competence. Objective of the current study is to evaluate and promote spatial perception of students using in the learning process principles of universal design for learning (UDL). As the result a model for development of design students spatial perception has been developed and approbated.